High-Resolution and Jamming-Resistant Adaptive Synthetic Aperture Radar Imaging System based on UWB-OFDM Waveform - Hossain, Md Anowar; Elshafiey, Ibrahim; Alkanhal, Majeed A. S. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A novel approach for jamming-resistant and high-resolution synthetic aperture radar (SAR) imaging technique is explored based on ultrawideband orthogonal frequency division multiplexing (UWB-OFDM) waveform. Suitable waveforms for both friendly and hostile environment are proposed based on various random sequences and tested for SAR imaging in presence of a digital radio frequency memory (DRFM) repeat jammer. Adaptivity factor is introduced to make the system consistent in both environments. Wide-band ambiguity function (WAF) has been derived and the effect of subcarrier composition in UWB-OFDM waveform as SAR signal is analyzed to avoid ambiguity in image reconstruction. Appropriate UWB-OFDM pulse shaping is introduced for SAR imaging in jamming scenarios and in hostile environments to solve the susceptibility of conventional linear frequency modulated (LFM) chirp signal, Gaussian pulses and any other constant pulse shape to avoid the possibility of false target introduced by jammer and to achieve secured imaging in jamming scenarios. The peak side-lobe performance is examined in terms of number of OFDM sub-carriers and sub-carrier orientation.